Premarital Counseling Affects Primigravidas’ Knowledge and Attitude on Reproductive and Sexual Health - Rika Ortiningsih; Kasiati Kasiati; Samsriyaningsih Handayani (Jurnal Ners, 2021)
Introduction: Unplanned pregnancy has been a worldwide issue, many of which end as unplanned abortions, miscarriages and deliveries. One-time premarital reproductive and sexual health counseling has been chosen as a program; however, its later effect on knowledge and attitude has not been evaluated. This study aimed to analyze the effectiveness of such premarital counseling for prospective brides on their knowledge and attitude during their first pregnancy.Methods: The exposed group of 20 and control group of 40 primigravida participants were selected consecutively. Questionnaires were distributed online using Google Form application to participants to gather data on premarital counseling attendance in the past, and current knowledge and attitude. The influences were tested with logistic regressions at the significance level (α) of .05.Results: There was influence of sexual and reproductive health counseling for the bride and groom on the knowledge (p = .036 OR = 8.480 95% CI = 1.153 - 62.346) and the attitude (p = .020 OR = 5.411 95% CI = 1.311 - 22.329).Conclusion: Premarital sexual and reproductive health counseling influenced primigravidas’ knowledge and attitude. The counselling should be intensified and extended to other cities to improve knowledge and attitude of primigravidas. Studies are needed to measure the effect of primigravidas’ knowledge of and attitude toward reproductive and sexual health on the outcome of the pregnancy.